COPYRIGHT ISSUES IN ELECTRONIC GAMES: A COMPARATIVE STUDY - Abhinaya Ramesh, Dr. Aradhana Satish Nair (Chelonian Research Foundation, 2023)
Video/ Electronic games are a type of modern art and perhaps one of the most contemporary ones. During the Pandemic lockdown, mobile, video, and internet games like "Ludo King" and "Call of Duty " increased significantly. Video/ Electronic games are intricate works of fiction that require players involvement, and this is done with the help of a computer programme on a specific hardware. They incorporate a variety of artistic elements, such as music, screenplays, stories, videos, artwork, and characters. Electronic games are therefore not produced as a single work but rather as a combination of distinct components, each of which may be protected by copyright provided it meets a particular standard of novelty and ingenuity. Article 2 of the Berne Convention states the subject matter of works covered under the copyright, video/ electronic games also have the characteristic features to fall under the ambit of subject matterof copyright based on that provision. This article explores whether the Indian Copyright Act provides a proper classification for electronic games since these games incorporate a lot of artistic elements, each of which falls under the subject matter of copyright, i.e., Graphical characters in the game comes under artistic work, musical elements in the game falls under musical work, the computer programme used in the game can be stated as literary work and the electronic games on the whole has the characteristics of a cinematograph film. The article aims to examine the lack of specific classification with respect to Copyright in Electronic Games in India by making a comparative analysis with foreign countries. Key Words: Electronic Games, Berne Convention, Indian Copyright Act, Artistic Work, Computer Programme, Cinematograph Film, Literary Work.